A Militância na identidade do CIMI - Simões, Maria Cecília dos Santos Ribeiro (Sacrilegens, 2009)
In this article we intend to develop a short presentation of Indigenous Missionary Council - CIMI - as an institution and its training context, within a line of militant Catholicism, to explain the formation of a specific identity in CIMI and also raise the discussion about Christian identity in relation to the mission. We propose a study of this identity simultaneously delimiting the directions and objectives most relevant for CIMI and the methodologies used to reach them.